(untitled) (Asian Journal of Medical and Biological Research, 2019)
Aging is one of the embryonic problems in Bangladesh and this has been gradually increasing with its far-reaching consequences. Elderly can develop new and complicating health problems. In most cases the diseases are chronic and complex. The structures were designed to investigate the health status, depression, and function of the daily living of the older men and women in the Sylhet region of Bangladesh. The data were collected using stratified sampling. We have used cross-sectional methods to analyze the data and performed a chi-square test to test the association and a then bivariate and multivariable logistic regression model was used to evaluate the major risk factors of CVD. In this study, 229 elderly people were considered aged from 60 to 60+ years-old face to face personal interviews. Among them 16.6% elderly are suffering in depression. According to residence, the condition of health is good in the ethnic group (21.9%) and this situation is worse in the rural group (97.5%). In addition, people who have depression were 0.087 times or 91.3% (OR = 1.115, 95% CI 0.273-4.552) less likely to have healthy compared to the people who did not have depression. In this study, we have seen that there were many factors that were associated with health status among different communities’ elderly people in Sylhet. This research will help clinicians and policymakers to develop appropriate strategies of CVD patients and organize health education programs for changing lifestyles among elderly in Sylhet. Asian J. Med. Biol. Res. June 2019, 5(3): 197-206